Measuring. Monitoring. Management. Control - D.E. Chikrin; K.R. Smolnikova; I.G. Galiullin (Измерение, мониторинг, управление, контроль)
Background. Collaborative robots are a major trend in various industry sectors as cobots transform workspaces and increase productivity. Ensuring safety in operator-cobot interactions is one of the key issues when introducing cobots into manufacturing. Materials and methods. This article reviews the main technical safety standards governing the design, installation and operation of cobots, such as: ISO 10218-1:2011; ISO/TS 15066:2016; ISO 10218-2:2011. The main part of the article analyses key aspects of collaborative robotics safety, including: risk assessment of scenarios of operator-cobot interaction in a collaborative workspace; principles of safe workspace design; technical means of safety (sensors, emergency stop systems, force and speed limitation); methods of validation and verification of cobot safety. The paper also analyses technological problems that cobotics defines and describes possible solutions in order to optimise the interaction between cobots and the operator as a whole. Results and conclusions. Compliance with the presented recommendations will not only minimize the risks associated with the use of cobots, but also unlock the full potential of collaborative robotics to create economical, safe and high-performance workplaces of the future.